1997
DOI: 10.1111/j.1399-0039.1997.tb02715.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at the TNF loci in rheumatoid arthritis

Abstract: The purpose of this work was to analyze the possible influence of TNF loci polymorphism on the susceptibility and/or the disease profile of rheumatoid arthritis (RA). Tumor necrosis factor (alpha and beta) genotypes were determined in 60 patients with RA and 102 healthy subjects by a method based on PCR-RFLP with amplification-created restriction sites. The results obtained in the present study showed that there is not a significant association of either TNF alpha promoter variation (at positions -308 and -238… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
1
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 31 publications
4
73
1
1
Order By: Relevance
“…For example, in a juvenile idiopathic arthritis cohort from Turkey, the -308 G-to-A polymorphism was associated with a poor clinical course (56). Vinasco et al (57) found more frequent nodular disease in their cohort of adult RA patients with the TNFA -308 AA plus AG genotypes. High levels of TNF␣ are associated with more severe disease in RA (58), and elevated levels of TNF␣ are found in the synovial fluid and synovial tissue of RA patients (25).…”
Section: Discussionmentioning
confidence: 89%
“…For example, in a juvenile idiopathic arthritis cohort from Turkey, the -308 G-to-A polymorphism was associated with a poor clinical course (56). Vinasco et al (57) found more frequent nodular disease in their cohort of adult RA patients with the TNFA -308 AA plus AG genotypes. High levels of TNF␣ are associated with more severe disease in RA (58), and elevated levels of TNF␣ are found in the synovial fluid and synovial tissue of RA patients (25).…”
Section: Discussionmentioning
confidence: 89%
“…24 Two subsequent Spanish studies also found no association between either À308 or À238 SNPs and susceptibility to RA. 25,26 A large study of Japanese RA patients (n ¼ 545) showed that while À308A was increased in RA patients, this increase was dependent on linkage to DRB1. 27 Another large Japanese study (n ¼ 387) looked at several TNF SNPs including À308, but only found that the T allele of the -857 SNP was increased in RA patients, and this link also proved to be dependent on HLA-DRB1*0405.…”
Section: Autoimmune Disease Associationsmentioning
confidence: 99%
“…[10][11][12][13] A major point of interest as to whether these cytokine markers can be related to human disease status 1,2,4-13 and studies in malignant 2 and autoimmune [4][5][6][7] disease have suggested that the TNF locus can contribute to disease susceptibility. Indeed, similar studies have demonstrated that IL-1 and IL-10 are also associated with the presence or severity of autoimmune diseases across a variety of ethnic backgrounds.…”
mentioning
confidence: 99%
“…While the majority of work in cytokine genetics has been carried out on the TNF locus, [2][3][4][5][6][7] other cytokines have also featured, notably IL-1 [8][9][10] and IL-10. [10][11][12][13] A major point of interest as to whether these cytokine markers can be related to human disease status 1,2,4-13 and studies in malignant 2 and autoimmune [4][5][6][7] disease have suggested that the TNF locus can contribute to disease susceptibility.…”
mentioning
confidence: 99%